Myopia: Mechanisms and Strategies to Slow Down Its Progression - Andrea Russo; Alessandro Boldini; Davide Romano; Giuseppina Mazza; Stefano Bignotti; Francesco Morescalchi; Francesco Semeraro (Journal of Ophthalmology)
This topical review aimed to update and clarify the behavioral, pharmacological, surgical, and optical strategies that are currently available to prevent and reduce myopia progression. Myopia is the commonest ocular abnormality; reinstated interest is associated with high and increasing prevalence, especially but not, in the Asian population and progressive nature in children. The growing global prevalence seems to be associated with both genetic and environmental factors such as spending more time indoor and using digital devices, particularly during the coronavirus disease 2019 pandemic. Various options have been assessed to prevent or reduce myopia progression in children. In this review, we assess the effects of several types of measures, including spending more time outdoor, optical interventions such as the bifocal/progressive spectacle lenses, soft bifocal/multifocal/extended depth of focus/orthokeratology contact lenses, refractive surgery, and pharmacological treatments. All these options for controlling myopia progression in children have various degrees of efficacy. Atropine, orthokeratology/peripheral defocus contact and spectacle lenses, bifocal or progressive addition spectacles, and increased outdoor activities have been associated with the highest, moderate, and lower efficacies, respectively.